Green marketing strategy, competitive advantage and firm performance in the hotel industry - Tiong, Ying Ying (2018)
The economic growth has stimulated the increasing income to the nation yet it followed by the environmental problem on the opposite side. This has aroused the global concern and people started to embrace green. Business opportunities have been created; meanwhile, it erodes firm's competitiveness if the current business is threatening to the environment. Thus, the present study in the green marketing standpoint seeks to examine the direct and indirect relationship between hotel's green marketing strategy (green brand building strategy and green service marketing mix), competitive advantage (differentiation and cost advantage) and firm performance (financial, social and quality, environmental performance). To bridge the gap of the study, the present study has proposed green procurement, green innovation, green brand communication and green employee empowerment to form green brand building strategy. Likewise, green service marketing mix has been tailored to the setting of the study. Data were collected from 110 green hotels and resorts in Malaysia and PLS-SEM was applied to evaluate the model of the study. Analysis of the direct relationship shows a significant effect of the hotel's green marketing (green brand communication, green promotion, green place, green process) on differentiation advantage and (green procurement, green employee empowerment and green physical evidence) on cost advantage. Besides, the direct relationship is significant between all the dimensions of competitive advantage and firm performance except the relationship between cost advantage and social and quality performance. Moreover, the result provides significant evidence on the indirect relationship between hotel's green marketing strategy (green procurement and green physical evidence) and financial performance; (green physical evidence) and environmental performance mediated by cost advantage. Also, indirect relationships found between green process and social and quality performance mediates by differentiation advantage. This study is important for researchers and practitioners as it provides new literature into the hotel's green marketing strategy and new insight to gain benefit from firm green practice.